Competitive Enhancement Assistance Through Patient-Oriented Marketing Strategy to ISHK Medica Eye Clinic Managerial Team in Batu City - Lussia Mariesti Andriany; Murtianingsih; Titania Dwiandini (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: Enhancing the competitiveness of ISHK Medica Eye Clinic through assistance in the marketing area, specifically patient-based orientation marketing strategies. Method: This community service was held through focus group discussion (FGD) with the managerial team of ISHK Medica Eye Clinic. The FGD was held two times: the first one explored the initial situation in the clinic, and the second one was purposed to assist the managerial team in terms of patient-based orientation marketing strategy. Practical Applications: The main output of this community service is marketing strategy based on the needs of patients. This strategy is willing to enhance the visibility of the clinic in the future so that potential patients will recognize this clinic as their healthcare option. Conclusion: Marketing strategy is significantly important for ISHK Medica Eye Clinic since they just launched their service in September 2025. This strategy should be continuously monitored since patients’ demand will change rapidly.